Consumer behavior for Sensodyne toothpaste GlaxoSmithKline Bangladesh LTD. - Islam, Rubana (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.